Dramatic and Cinematic Potentials of the Fifth Dome in Nizami's Haft Peykar - Heydar Ali Dahmarde; Hojat Raeisi (Literary Arts)
In contemporary eras, considerable emphasis is placed globally on the adaptation of literary works. Artists in various fields, including performing arts, cinema, visual arts, etc., each employing their unique approaches, have drawn inspiration from these works, resulting in the creation of notable and prominent pieces. Among these artistic endeavors, cinema, being a comprehensive form of art with enhanced capabilities relative to other media, has played a significant role in the realm of literary adaptations. Nevertheless, in Iran, despite its wealth of literary works, there has been relatively limited attention devoted to literary adaptations. An exemplary instance of adaptation characterized by imagination and allegory is Nezami's Haft Peykar. Given the allure that works featuring elements of imagination, allegory, and symbolism hold for adaptation in visual arts, particularly in cinema, this study aims to explore the potential for theatrical and cinematic adaptation within the framework of Nezami's Haft Peykar, focusing specifically on its ‘Fifth Dome’. The diverse array of imagery, vivid descriptions, robust narrative structure, exceptional characters, and engaging conflicts and suspensions collectively contribute to rendering this narrative amenable to a compelling and respectable film adaptation. Keywords: Theatrical Aspects, Cinematic Adaptation, Haft Paykar, Fifth Dome, Imaginary-allegorical. IntroductionNizami Ganjavi, a 12th-century poet, gained widespread recognition through his quintet known as "Five Treasures" (Panj Ganj), among which Haft Peykar shines prominently. This poem is celebrated for its unique structure—a story within a story—and is considered by many poets and scholars, both in Iran and globally, as one of the most exquisite poems in the Persian language. Haft Peykar blends fiction with historical events from the life of Bahram Gur, skillfully weaving reality with poetic creation. It can be broadly categorized into two main sections. The first section encompasses the beginning and ending of the book, detailing the life of Bahram V, a Sassanid emperor, from his birth to his death. This part employs a historical narrative style. The second central section of the book diverges into the realm of fiction, presenting seven tales narrated by Bahram’s seven wives. These wives are princesses from the seven different climes, each representing a unique cultural background. Nizami crafts Bahram, the protagonist, as a multifaceted ruler—wise, intelligent, prudent, chivalrous, just, passionate, and optimistic. The narrative unfolds with Bahram falling in love with these princesses upon seeing their portraits. After his ascent to the throne, he ambitiously pursues their affections, eventually succeeding in marrying each one. For each wife, he constructs a distinct palace where, nightly, one of the princesses regales him with a story, weaving a tapestry of narratives that enrich the overarching plot.Interestingly, each palace in Haft Peykar is uniquely characterized by a specific color, which extends to the princesses' attire and the palace furnishings. These colors correspond to different days of the week, enhancing the thematic richness of the narrative. After listening to the stories each night, Bahram embraces the storytelling princess and falls asleep. The colorful domes of the palaces recall the walls of Ecbatana as described by Herodotus in his accounts of the Median kings, suggesting a continuation of this aesthetic preference and opulence in ancient royal courts. Similarly, the varied hues in the king's clothing echo historical accounts of past monarchs’ colorful attire. Furthermore, the association of colors with the days of the week draws on ancient superstitions and traditions about celestial bodies. The tales spun by the princesses are highly imaginative, imbued with elements that stretch the bounds of belief. In many scenes of literary adaptations, characters seem to float ethereally, as if moving within a realm of dreams. Since the earliest days of cinema, adapting literary works has been a vital bridge between literature and film, contributing significantly to the development of the cinematic arts. Forms of art that share a close relationship with literary narratives, like cinema, benefit greatly from this connection.Numerous scholarly works, including books, articles, and theses, have addressed the dramatic and adaptable aspects of classical literary texts. Notable among these are Dramatic Aspects of Masnavi by Kohansal (2011), Tarikh-e Bayhaqi: A Cinematic Narrative by Pourshabanian (2013), and Dramatic Aspects of Kalila and Dimna by Shirmardi (2016). However, there appears to be no existing research specifically on the dramatic aspects of the fifth dome of Nizami Ganjavi's Haft Peykar for adaptation into an imaginative-allegorical film. This study may, therefore, represent the first investigation of its kind in this area. Materials and MethodsIn this research, a descriptive-analytical method was employed. The study began by reviewing a range of sources related to literature, theater, cinema, and literary adaptation, taking detailed notes from these materials. Virtual space resources also proved invaluable in supplementing the findings. Subsequently, we classified and analyzed these notes to develop a systematic framework for the research. This structured approach facilitated a thorough exploration of the topic at hand. Research FindingsAs a relatively new art form, cinema has forged a deeper link with literature than many other arts, due to its novelty and its inherently linear and literary narrative structure. Today in Iran, with its rich cultural and literary heritage, there is a clear need to explore the dramatic potential of Persian literature for producing compelling and content-rich films. This need is particularly urgent given the technical advancements in cinema and the scarcity of original and engaging subject matter. Adapting literary works not only preserves cultural heritage but also enriches the cinematic landscape with profound and captivating stories. Although the connection between literature and cinema emerged in Iran alongside other parts of the world, Iranian filmmakers have historically paid little attention to adapting the country's classical and valuable literature. Compared to global efforts, adaptations from Iranian literature have been relatively sparse. Despite this, the story of the fifth dome in Nizami Ganjavi's Haft Peykar holds significant potential for transformation into a notable theatrical and cinematic adaptation. Discussion of Results and ConclusionThis particular story, with its imaginative and allegorical nature, features a coherent and strong narrative that is crucial for successful adaptation. The presence of common elements of story and drama, such as characters, plot, ideas, setting, and the use of successive and sometimes nested narratives, could greatly enhance the suspense and overall appeal of the work, making it a compelling candidate for adaptation into film or theater. Moreover, the vivid imagery and scenes that highlight the imaginative aspect of the work, along with fantastic creatures and surreal environments, could pave the way for a fantasy film rich in engaging narratives and strong dramatic elements. Exciting sequences, paired with a captivating storyline and sophisticated special effects, could culminate in an artistic and popular film. This adaptation would not only transport audiences into a poetic realm but also remain true to the poet's original vision of crafting a meaningful story replete with vivid imagery. Additionally, the intense suspense and conflicts inherent in the story make it an ideal candidate for transformation into a compelling imaginative-allegorical film, likely to resonate with contemporary audiences. This combination of suspense and conflict underscores the potential for this narrative to become a standout cinematic experience that captivates modern viewers.